Costs and benefits of investing in transformative care policy packages: A macrosimulation study in 82 countries - Jérôme De Henau (International Labour Organization (ILO), 2022)
This study examines the annual investment required for universal, collectively funded childcare and longterm care services, as well as adequate paid care leave and breastfeeding breaks to parents in 82 countries. Simulations of policy reforms show that extending paid leave and breastfeeding breaks to all employed parents (including those in informal employment) at an adequate level of pay would require about 0.3 per cent of GDP of annual investment by 2035. Extending universal childcare would require additional annual investment of 1.5 per cent of GDP by 2035 over and above current public spending of 0.3 per cent. For long-term care, the annual additional investment by 2035 would be 2.5 per cent of GDP, over and above current public spending of 0.6 per cent. Such care investments could also provide powerful economic stimulus, creating up to nearly 300 million jobs by 2035, and recouping some of the investment through increased tax revenue.
Keywords: C67; H51; J16; 330; family leave; maternity protection; maternity benefits; maternity leave; parental leave; childcare; long-term care services; care economy; social infrastructure; economic stimulus; investment; input-output analysis; gender equality; sustainable development goals